Unveiling the Semiotics of Cigarette Advertising: Analyzing Propaganda Strategies - Tano, Andreas; Simanjuntak, Immanuel Sheva (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2023)
This study aims at demonstrating how prolonged exposure to media, particularly in cigarette ads, can shape individuals' beliefs, attitudes, and values. The cultivation theory by Gerbner, G. (1998) was applied in the analysis to show the mentioned issues. Besides, the study also investigated the role of cinematography, specifically cameraworks, and employed a semiotic approach to explore signs and symbols in the ads. Ferdinand de Saussure's (1916)